Optimizing Patient Selection for Endovascular Treatment in Acute Ischemic Stroke (SELECT): A Prospective, Multicenter Cohort Study of Imaging Selection. Issue 3 (21st January 2020) - Sarraj, Amrou; Hassan, Ameer E.; Grotta, James; Sitton, Clark; Cutter, Gary; Cai, Chunyan; Chen, Peng R.; Imam, Bita; Pujara, Deep; Arora, Ashish; Reddy, Sujan; Parsha, Kaushik; et al.
Abstract : Objective: The primary imaging modalities used to select patients for endovascular thrombectomy (EVT) are noncontrast computed tomography (CT) and CT perfusion (CTP). However, their relative utility is uncertain. We prospectively assessed CT and CTP concordance/discordance and correlated the imaging profiles on both with EVT treatment decisions and clinical outcomes. Methods: A phase 2, multicenter, prospective cohort study of large‐vessel occlusions presented up to 24 hours from last known well was conducted. Patients received a unified prespecified imaging evaluation (CT, CT angiography, and CTP with Rapid Processing of Perfusion and Diffusion software mismatch determination). The treatment decision, EVT versus medical management, was nonrandomized and at the treating physicians' discretion. An independent, blinded, neuroimaging core laboratory adjudicated favorable profiles based on predefined criteria (CT:Alberta Stroke Program Early CT Score ≥ 6, CTP:regional cerebral blood flow (<30%) < 70ml with mismatch ratio ≥ 1.2 and mismatch volume ≥ 10ml). Results: Of 4, 722 patients screened from January 2016 to February 2018, 361 patients were included. Two hundred eighty‐five (79%) received EVT, of whom 87.0% had favorable CTs, 91% favorable CTPs, 81% both favorable profiles, 16% discordant, and 3% both unfavorable. Favorable profiles on the 2 modalities correlated similarly with 90‐day functional independence rates (favorable CT = 56% vs favorable CTP = 57%, adjusted odds ratio [aOR] = 1.91, 95% confidence interval [CI] = 0.40–9.01, p = 0.41). Having a favorable profile on both modalities significantly increased the odds of receiving thrombectomy as compared to discordant profiles (aOR = 3.97, 95% CI = 1.97–8.01, p < 0.001). Fifty‐eight percent of the patients with favorable profiles on both modalities achieved functional independence as compared to 38% in discordant profiles and 0% when both were unfavorable ( p < 0.001 for trend). In favorable CT/unfavorable CTP profiles, EVT was associated with high symptomatic intracranial hemorrhage (sICH) (24%) and mortality (53%) rates. Interpretation: Patients with favorable imaging profiles on both modalities had higher odds of receiving EVT and high functional independence rates. Patients with discordant profiles achieved reasonable functional independence rates, but those with an unfavorable CTP had higher adverse outcomes. Ann Neurol 2020;87:419–433